Acceptance of gold as an alternative currency: an empirical validation of adoption of innovation theory - Yusuf, Muhammad-Bashir; Meera, Ahamed Kameel Mydin; Mat Ghani, Gairuzazmi; Abdul Manap, Turkhan Ali; Larbani, Moussa (University of Malaya, 2015)
This study aims to examine the determinants of gold dinar adoption in Kelantan, Malaysia by using an extended adoption model which consists of seven factors: relative advantage, triability, result visibility, result demonstrability, anxiety, facilitating conditions, and trust. Survey data collected from gold dinar adopters in Kelantan were used to identify the components of the gold dinar adoption and its determinants. Structural equation modeling technique was employed to test whether the hypothesised model fits the data collected. This study finds that all the indicators have good loading on their factors, suggesting that they measure what they were supposed to measure. All the factors except ‘trust’ are found to influence the adoption of the gold dinar. Thus, the adoption of gold dinar would depend more on its embedded benefits, religious link and the removal of impediments attached to it and not necessarily, the trust which users may place in issuing authorities.